Penerapan Digital Marketing Dalam Meningkatkan Penjualan Produk Sneakers Pada Pt Mutasis Group Indonesia - Mustafa, Hidayah Putra; Thamrin, Djuni; Siahaan, Matdio Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of digital marketing in increasing the sales of sneaker products at PT Mutasis Group Indonesia. The company utilizes various digital platforms such as Instagram, TikTok, Facebook, and Shopee to expand its market reach. This research employs a descriptive qualitative method with data collected through observation, interviews, and documentation involving the owner and employees of PT Mutasis Group Indonesia. The findings reveal that active and consistent digital marketing strategies significantly contribute to increased sales, especially in stores that apply these strategies optimally, such as SneakersMust. The company faces several challenges, including limited human resources, insufficient content creation equipment, and frequent changes in social media algorithms. Nevertheless, digital marketing has proven effective in enhancing customer loyalty and boosting sales by up to 50%. This study recommends strengthening the implementation of digital marketing across all stores under the company to support overall business performance.